The p53 network: cellular and systemic DNA damage responses in cancer and aging - Vaddavalli, Pavana Lakshmi; Schumacher, Björn (Trends in genetics, 2022)
The tumor protein TP53 gene, encoding the cellular tumor antigen p53, is the single most frequently mutated gene in human cancers. p53 plays a central role in responding to DNA damage and determines the outcome of the DNA damage checkpoint response by regulating cell cycle arrest and apoptosis. As a consequence of this function, dysfunctional p53 results in cells that, despite a damaged genome, continue to proliferate thus fueling malignant transformation. New insights have recently been gained into the complexity of the p53 regulation of the DNA damage response (DDR) and how it impacts a wide variety of cellular processes. In addition to cell-autonomous signaling mechanisms, non-cell-autonomous regulatory inputs influence p53 activity, which in turn can have systemic consequences on the organism. New inroads have also been made toward therapeutic targeting of p53 that for a long time has been anticipated. The tumor protein TP53 is the single most frequently mutated gene in human cancer.p53 is a central regulator of the DNA damage response that impacts cancer and aging.p53 is regulated by non-cell-autonomous mechanisms and exerts systemic consequences.Therapeutic strategies targeting p53 in cancer have recently made significant progress.